Editorial: Estabilidad empresarial: un factor clave en la recuperación económica (2021)
During the last few years, economic growth, driven by business strengthening, has been one of the pillars of public policies in different countries, to which Colombia has been no stranger. From this perspective, and within the framework of the globalized economic system, the implementation of the International Financial Reporting Standards - IFRS - brings new questions and challenges for companies. Thus, corporate financial stability has become a fundamental factor to strengthen and guarantee their growth, allowing them to face, overcome and overcome the difficulties of the changing global economic context. In this sense, the declaration of pandemic in March 2020, by the World Health Organization - WHO, imposed to the global economic system, to governments and particularly to the business sector, new challenges in terms of management, innovation and resource management, in order to overcome the effects on the economic activity and the imminent imminence of the pandemic. on economic activity and the impending crisis. This invites reflection on the adoption of measures to avoid the rapid deceleration of economic activity and its disastrous consequences for society, further motivating interdisciplinary and intersectoral dialogue for the sustainable management of resources and the minimization of risks and losses. Considering this, at the regional level, companies are faced with a difficult path to survive in the current crisis. This forces them to rethink some goals and, at the same time, invites them to review their processes in order to find strengths and opportunities, as well as to innovate and manage innovation in order to respond to the complex problems they face, thus playing a constructive role in the recovery of national economic activity, in addition to being a mitigating factor of the impact of the current crisis. This constructive role requires a historical review to reaffirm the importance of small and medium-sized regional enterprises, not only in their contribution to national production but also to socioeconomic development. Thus, guaranteeing the solvency and stability of these companies facilitates the viability of policies to return to the path of growth, making it possible to recover economic activity in a shorter period of time. Financial management becomes more relevant to mitigate, to a certain extent, the vulnerability caused by the reduction of income, revealing the urgent need to mitigate the negative effects of the strong deceleration of production and consumption that companies are currently enduring. With this panorama, In Vestigium Ire Magazine, once again, presents a series of articles, fruit of the research process of the authors, where they expose, in a very detailed and assertive way, analysis and reflections regarding business stability and strengthening, focused on small and medium enterprises in different sectors and regions of the Colombian economy, thus reiterating the commitment of the Universidad Santo Tomás to promote the dialogue of knowledge and provide solutions to the problems of the context.